What about parents? A systematic review of paediatric intensive interdisciplinary pain treatment on parent outcomes. (16th June 2022) - Harbeck‐Weber, Cynthia; Sim, Leslie; Morrow, Allison S.; Murad, M. Hassan
Abstract: Background and Objective: Intensive interdisciplinary pain treatment (IIPT) for youth with high impact chronic pain has been found to be effective in improving child symptoms and functioning. However, it remains unclear how these interventions impact the parents' own well‐being, as well as cognitions and behaviours which are known to influence child pain and functioning. Thus, the current study sought to determine the effect of IIPT on parent mental health, cognitions and behaviours in parents of youth attending IIPT with their child. Databases and Data Treatment: A search of the electronic databases CINAHL, Ovid EBM Reviews, Embase, Medline, APA PsychINFO, Scopus and web of Science was conducted. Studies were included if they comprised at least 10 parents of patients aged 9–22 with nonmalignant chronic pain attending an IIPT and were written in English. Results: A random‐effects model was used to pool the standardized mean change (SMC) across seven prepost studies. At discharge, IIPT participation was associated with small to moderate improvements in direct parental outcomes (general mental health, anxiety, depression and parenting stress), a moderate improvement in pain catastrophizing and large improvements in psychological flexibility and parenting behaviours. Most improvements were maintained at follow‐up. The risk of bias of all studies was rated as serious and the certainty of the evidence as low, suggesting limited confidence in the estimates. Conclusions: Although parents appear to benefit from attending an IIPT with their child, RCTs are needed to substantiate the effect of these interventions on important aspects of parent well‐being and functioning.